The relationship of cognitive flexibility and conflict response type of senior school and university students - Smirnova, Yuliya S.; Dovgilovich, Ales E. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The problem of cognitive determination of conflict behaviour is analysed in the article. Cognitive flexibility is considered as an element of the cognitive component of conflict competence contributing to the using optimal conflict behaviour strategies. The results of the empirical study of the relationship between cognitive flexibility and conflict response type of senior school and university students are presented in the article. The high level of cognitive flexibility are associated with studentsʼ tendency to choose the optimal type of conflict response – conflict solution. The low level of cognitive flexibilty is associated with the choice of non-optimal types of response in the conflict – aggression and avoiding.
Keywords: conflict; conflict behaviour; type of conflict response; cognitive flexibility; senior school students; university students